Nonlinear buckling responses of a confined liner reinforced by functionally graded graphene with atom vacancy defects under thermal-mechanical loading - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Engineering Structures, 2026)

Buckling of the constrained subsea FGP-GPLs liner under pressure loading and heating field based on multi-source data fusion scheme - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Ocean Engineering, 2026)

Study on the removal effect of Enteromorpha polysaccharide on heavy metal-organic composite pollution - Xue Shen; Yingqiang Li; Meiling Li; Yaru Zai; Xue Han; Shida Zhang; Jin Wang; Zhigang Yang; Yang Song (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal temperature variations induced by urban extreme heat events at the micro-scale - Huifang Li; Shuman Shen; Meiling Gao; Yu Wu; Zhihua Wang; Huanfeng Shen (Urban Climate, 2026)

Computed method for the thermal buckling performance of a constrained non-circular heated pipeline with an oval inverted arch - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Tunnelling and Underground Space Technology, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Comparison of efficacy and safety of dual orexin receptor antagonists lemborexant and daridorexant for the treatment of insomnia: a systematic review and meta-analysis - Ming Tang; Ziyi Shen; Peilu Yu; Meiling Yu; Xiaoqiong Tong; Guohui Jiang (Psychopharmacology, 2025)

Hypoxia-activated and status-reversing hydrogel platform initiates potent systemic immunity against triple-negative breast cancer - Zhike Li; Xianzhou Huang; Jin Yang; Meiling Shen; Yanjie You; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Analytical and numerical study on the dynamic responses of the buried offshore oval lined-pipeline system under strike-slip fault - Zhaochao Li; Shiyi Zhang; Meiling Shen; Hao Huang (Ocean Engineering, 2024)

Thermal upheaval buckling framework of a graphene-reinforced subsea pipeline laid on an arched concave seabed - Zhaochao Li; Di Hu; Meiling Shen; Hao Huang; Zhihua Ou (Engineering Structures, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

A jellyfish robot based on two-bar and four-spring tensegrity structures - Jianwei Sun; Changjian Li; Meiling Zhang; Lu Shen; Siyang Gao (Ocean Engineering, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Exposure to ambient air pollutants is associated with an increased incidence of hyperuricemia: A longitudinal cohort study among Chinese government employees - Lidan Duan; Muyang Zhang; Yuhan Cao; Yuwei Du; Meiling Chen; Rumeng Xue; Minxue Shen; Dan Luo; Shuiyuan Xiao; Yanying Duan (Environmental Research, 2023)

Insight into the molecular mechanism of phosphine toxicity provided by functional analysis of cytochrome b5 fatty acid desaturase and dihydrolipoamide dehydrogenase in the red flour beetle, Tribolium castaneum - Xu Shen; Meiling Che; Honglei Xu; Xinbo Zhuang; Erhu Chen; Peian Tang; Kangxu Wang (Pesticide Biochemistry and Physiology, 2023)

A Two-Stage Network Based on Transformer and Physical Model for Single Underwater Image Enhancement - Yuhao Zhang; Dujing Chen; Yanyan Zhang; Meiling Shen; Weiyu Zhao (Journal of Marine Science and Engineering, 2023)
The absorption and scattering properties of water can cause various distortions in underwater images, which limit the ability to investigate underwater resources. In this paper, we propose a two-stage network called WaterFormer to address this issue using deep learning and an underwater physical imaging model. The first stage of WaterFormer uses the Soft Reconstruction Network (SRN) to reconstruct underwater images based on the Jaffe–McGramery model, while the second stage uses the Hard Enhancement Network (HEN) to estimate the global residual between the original image and the reconstructed result to further enhance the images. To capture long dependencies between pixels, we designed the encoder and decoder of WaterFormer using the Transformer structure. Additionally, we propose the Locally Intended Multiple Layer Perceptron (LIMP) to help the network process local information more effectively, considering the significance of adjacent pixels in enhancing distorted underwater images. We also proposed the Channel-Wise Self-Attention module (CSA) to help the network learn more details of the distorted underwater images by considering the correlated and different distortions in RGB channels. To overcome the drawbacks of physical underwater image enhancement (UIE) methods, where extra errors are introduced when estimating multiple physical parameters separately, we proposed the Joint Parameter Estimation method (JPE). In this method, we integrated multiple parameters in the Jaffe–McGramery model into one joint parameter (JP) through a special mathematical transform, which allowed for physical reconstruction based on the joint parameter (JP). Our experimental results show that WaterFormer can effectively restore the color and texture details of underwater images in various underwater scenes with stable performance.

A Quad-Functional On-demand released nanomissile achieves cascade amplification therapy of Triple-Negative breast cancer through reversing multiple resistance - Yan Wang; Xianzhou Huang; Shunyao Zhu; Lu Li; Jin Yang; Jie Li; Li Wang; Shuang Ma; Meiling Shen; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2023)

Morphological and endogenous phytohormone changes during long-term embryogenic cultures in Korean pine - Yan Liang; Xin Xu; Hailong Shen; Meiling Gao; Yan Zhao; Xue Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Mechanism of interactions between α-conotoxin RegIIA and carbohydrates at the human α3β4 nicotinic acetylcholine receptor - Meiling Zheng; Han-Shen Tae; Liang Xue; Tao Jiang; Rilei Yu (Marine Life Science & Technology, 2022)
Conotoxins are marine peptide toxins from marine cone snails. The α-conotoxin RegIIA can selectively act on human (h) α3β4 nicotinic acetylcholine receptor (nAChR), and is an important lead for drug development. The high-resolution cryo-electron microscopy structure of the α3β4 nAChR demonstrates several carbohydrates are located near the orthosteric binding sites, which may affect α-conotoxin binding. Oligosaccharide chains can modify the physical and chemical properties of proteins by changing the conformation, hydrophobicity, quality and size of the protein. The purpose of this study is to explore the effect of oligosaccharide chains on the binding modes and activities of RegIIA and its derivatives at hα3β4 nAChRs. Through computational simulations, we designed and synthesized RegIIA mutants at position 14 to explore the importance of residue H14 to the activity of the peptide. Molecular dynamics simulations suggest that the oligosaccharide chains affect the binding of RegIIA at the hα3β4 nAChR through direct interactions with H14 and by affecting the C-loop conformation of the binding sites. Electrophysiology studies on H14 analogues suggest that in addition to forming direct interactions with the carbohydrates, the residue might play an important role in maintaining the conformation of the peptide. Overall, this study further clarifies the structure–activity relationship of α-conotoxin RegIIA at the hα3β4 nAChR and, also provides important experimental and theoretical basis for the development of new peptide drugs.

Pigment profile and gene analysis revealed the reasons of petal color difference of crabapples - Ting Shen; Meiling Han; Qianrui Liu; Chen Yang; Jiaxin Meng; Houhua Li (Brazilian Journal of Botany, 2021)

Natural population re-sequencing detects the genetic basis of local adaptation to low temperature in a woody plant - Yanmin Hu; Xianjun Peng; Fenfen Wang; Peilin Chen; Meiling Zhao; Shihua Shen (Plant Molecular Biology, 2021)

A tale of two cities: different urban heat mitigation efficacy with the same strategies - Meiling Gao; Fei Chen; Huanfeng Shen; Huifang Li (Theoretical and Applied Climatology, 2020)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Genome-wide investigation of microsatellite polymorphism in coding region of the giant panda (Ailuropoda melanoleuca) genome: a resource for study of phenotype diversity and abnormal traits - Meiling Cheng; Jianying Ren; Fujun Shen; Yan Huang; Zhenxin Fan; Megan Price; Bisong Yue; Xiuyue Zhang (Mammal Research, 2019)

Multiple timescale analysis of the urban heat island effect based on the Community Land Model: a case study of the city of Xi’an, China - Meiling Gao; Huanfeng Shen; Xujun Han; Huifang Li; Liangpei Zhang (Environmental Monitoring and Assessment, 2018)

Dissecting the complex molecular evolution and expression of polygalacturonase gene family in Brassica rapa ssp. chinensis - Ying Liang; Youjian Yu; Xiuping Shen; Heng Dong; Meiling Lyu; Liai Xu; Zhiming Ma; Tingting Liu; Jiashu Cao (Plant Molecular Biology, 2015)

Cloning and structure of a histocompatibility class IIA gene (Lelo-DAA) in Chinese longsnout catfish (Leiocassis longirostris) - Tong Shen; Xiaoshun He; Meiling Lei; Jingru Wang; Xiuming Li; Jianming Li (Genes & Genomics, 2014)